Sound Governance Analysis: Local Government Partnership Model In Village Community Empowerment - Suryoto Suryoto; Paulus Israwan Setyoko; Ranjani Ranjani Ranjani (Universitas Sultan Ageng Tirtayasa, 2022)
Sound governance reviews the partnership model between regions and civil society and international actors. International actors used as the unit of analysis in this study are PT Hyup Syung Purbalingga. This research is motivated by the results of a preliminary pre-survey, namely the absence of sustainability in the Padamara Village Community Empowerment Program conducted based on a partnership between the Padamara village government, PT Hyup Sung, and the Bojanegara Village Community. This study will further analyze the issue of partnership in Bojanegara Village Community Empowerment from a sound governance perspective, focusing on the involvement of PT Hyup Syung as an international actor in the process. This study is a type of descriptive research with a qualitative approach. Data obtained through key informants (key people) are determined purposively (purposive). The key person in this study is the executor of the Local Government, while other informants are some officials from PT. Hyup Sung Indonesia, and the villagers who were touched by the program were then determined by a snowball. In addition, documentation and observation studies are also used to capture relevant data. The presence of international parties participating in community empowerment in Indonesia, especially in the Purbalingga Regency, has not been realized as a potential. This is due to the limited resources of local governments as the sole actor in development, which should force the government to maximize any potential resource support from outside sources, whether private, public, or international. The form of partnership is an ideal desired by sound governance but has not been understood by the government at both the Purbalingga Regency government level and the Bojanegara village government level. In other words, positive partnerships between local governments, village governments, and NGOs have not occurred under the management of PT. Hyup Sung Indonesia.